Exploration of Consumer Preferences: Sensory Evaluation of Synbiotic Yoghurt with Honey - Suharto, El Latifa Sri; Ferawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
This study aims to ascertain the sensory characteristics of yogurt when honey is added at varying concentrations. The sensory characteristics observed include colour, aroma, taste and texture. In this study, the treatment is the addition of honey (P1) at 0%, (P2) at 2.5%, (P3) at 5%, (P4) at 7.5% and (P5) at 10% to the manufacture of yogurt. The results demonstrated that adding honey had a statistically significant impact (P < 0.05) on the sensory quality of yogurt. The hedonic test of yogurt indicated that the addition of honey was a favorable attribute by the panelists, who considered it an effective alternative to sugar as a sweetener. The hedonic test values obtained were as follows: colour (3.2-3.77); aroma (3.13-4.18); taste (2.08-4.53); texture (3.28-3.88). Based on these results, it can be concluded that the optimal treatment was achieved in the yogurt with the addition of 10% honey.